2021
DOI: 10.33206/mjss.819453
|View full text |Cite
|
Sign up to set email alerts
|

PERT Simülasyon Yöntemiyle Denizyolu Lojistiği İhracat Süreç Analizi

Abstract: ÖzUluslararası ticaretin en yoğun olarak gerçekleştiği mod olan denizyolu taşımacılığındaki lojistik süreçlerin etkin ve verimli bir biçimde koordine edilmesi, karmaşık bir yapıyı barındırdığından önemli olmaktadır. Bu sürecin iyi yönetilmesi ile aksaksız bir biçimde sürecin işlemesi mümkündür. Bu kapsamda çalışmada ülkelerin ekonomisinde önemli bir rol oynayan ihracat yüklerinin denizyolu taşıma süreci ele alınmıştır. FOB teslim şekli kapsamında ihracatçının sorumluluğu göz önüne alınarak, geminin bordasına k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Bruzzone et al (2012) used a simulation model of a real container terminal's process, together with genetic algorithms, to perform a range allocation optimization on the assignment of berths to incoming ships and the number of tractors to serve each dock crane. Bayar and Akan (2020) used Monte Carlo Simulation methods to analyze the business process of ocean freight pricing while Bayar and Akan (2021) used fuzzy program evaluation and review technique (PERT) to analyze the business process of export-import inland haulage in maritime logistics. Borch and Batalden (2015) showed that organizations may need to introduce entrepreneurial BPMJ 29,4 business models with strong links to external actors to tackle the logistics challenges of turbulent environments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bruzzone et al (2012) used a simulation model of a real container terminal's process, together with genetic algorithms, to perform a range allocation optimization on the assignment of berths to incoming ships and the number of tractors to serve each dock crane. Bayar and Akan (2020) used Monte Carlo Simulation methods to analyze the business process of ocean freight pricing while Bayar and Akan (2021) used fuzzy program evaluation and review technique (PERT) to analyze the business process of export-import inland haulage in maritime logistics. Borch and Batalden (2015) showed that organizations may need to introduce entrepreneurial BPMJ 29,4 business models with strong links to external actors to tackle the logistics challenges of turbulent environments.…”
Section: Literature Reviewmentioning
confidence: 99%